Hybrid Energy Management System Consisting of Battery and Supercapacitor for Electric Vehicle - Chavda, Jiten K; Prajapati, Smit; Vibhakar, Chirag; Patel, Nikunj; Shah, Varsha A (International Journal of Integrated Engineering, 2022)
This paper is mainly focused on Hybrid Energy Management System (HEMS) consisting of Battery (BT) and Super capacitor (SC). Two energy sources connected in with same DC link in parallel manner with the help of Bidirectional DC-DC converter, which is used to separate control of power flow of each source. Here Permanent magnet dc motor (PMDC) motor used as a load and speed control of PMDC motor can be done by PWM method for this purpose chopper circuit is used. Input of chopper circuit is DC link and output of the chopper is given to PMDC motor. This method of energy management gives power splitting between two sources based on State of Charge (SOC) of each individual source during different state of vehicle such as acceleration, constant running and deceleration. Improved filter-based power splitting techniques is implemented. Three acceleration reference points were taken for power splinting at different SOC levels of both energy sources. Objective of this proposed method is best use of both the sources i.e. battery and supercapacitor and maximum use of supercapacitor energy at the time of transient conditions. Battery supply energy during normal running condition or very less load condition. Hence during transient condition SC directly react with system and gives peak power requirement, so stress on battery is reduces hence lifetime of battery is increase, also power available during braking is store in SC and battery, so independence of Electric Vehicle (EV) is increases. Because of less peak power requirement, batteries with less peak output power is used so it is reduced size and cost of batteries. Matlab- Simulink software is used for simulation and also small scale hardware is also implemented of proposed method.